The reality of transformational leadership among public school principals in Jordan from the point of view of the evaluators of the Education Quality and Accountability Unit - Aladamat, Ebtesam Awwad (Journal of Educational and Psychological Sciences, 2021)
This study aimed to know the reality of transformational leadership among public school principals in Jordan from the point of view of the evaluators of the Education Quality and Accountability Unit, and to achieve the goal of the study, the researcher used the descriptive and analytical approach, the study tool represented in a questionnaire applied to a random sample of (50) male and female evaluators. The results of the study showed that the degree of transformational leadership practice of public school principals in Jordan came with a degree of approval (medium) and average of (3.33). As for the areas of transformational leadership, the field of individual considerations ranked first with a degree of approval (large) with an average of (3.53), followed by The field of the inspirational stimulus with a degree of approval (medium) with an average (3.33), then the field of the ideal effect with a degree of approval (medium) and average of (3.29), while the field of intellectual arousal ranked last with a degree of approval (medium) and with an average of (3.17), and in light of the results, the researcher presented a set of recommendations and proposals to improve the practice of public school principals and directors in Jordan, the most important of which are: Holding training courses and programs for each of the school principals and their teachers and their development to increase their capacity To practice transformational leadership.
Keywords: public school principals; transformational leadership; evaluators of the Education Quality and Accountability Unit